An epidemiological study of a patient population, triage category allocations and principal diagnosis within the emergency centres of a private healthcare group in the Emirate of Dubai, United Arab Emirates - Enrico Dippenaar (Wiley, 2020)
Abstract Aim To describe, compare and correlate the number of patients seen, their demographics, triage category allocations and principal diagnosis in four emergency centres; to better understand the patient population and triage practices in this setting. Design An observational, cross‐sectional, epidemiological study. Methods Electronic medical records were retrospectively evaluated from patients triaged in each of the four emergency centres over six months. Descriptive statistics were used to describe the patient demographics and variance between triage category allocations. Results A total of 56,984 patient records were captured, with an equal gender split and the workforce being the largest patient population (20-50 years). Acute upper respiratory infection was the most prolific diagnosis, and lower acuity triage categories were allocated the most. There were inconsistencies in the application of triage systems between the emergency centres, the most obvious being the variance in triage system selection and application.